Pengaruh Hedonic Motivation dan Utilatarian Motivation Terhadap Impulsive Buying pada Pengguna E-Commerce. - As'ad Khair; Kurniawati; Renny Lia Yustika; Siti Rohmah (FEB Universitas Sam Ratulangi Manado, 2023)
ABSTRACT This research aims to analyze the significant effect from hedonic motivation against impulsive buying on e-commerce consumers. Hedonic motivation and utilitarian motivation can encourage impulsive buying behavior in transactions when people shopping in e-commerce. This might be seen from several types of goods purchased in e-commerce, for instance, daily needs (foods and beverages), fashion, cosmetics, also travel needs (ticket for transportation and hotels). This study uses purposive sampling and questionnaire methods. This research was conducted on 344 respondents who are active users of social media and e-commerce users, such as Shopee, Tokopedia and Lazada. Data analyzed with Structural Equation Modelling (SEM) method and SMART-PLS application. The results shows that external factor has a positive influence on hedonic motivation and utilitarian motivation, it can be seen that hedonic motivation has a positive effect on impulsive buying factors, and utilitarian motivation does not affect impulsive buying. In addition, interpersonal factors and external factors have a significant positive effect on impulsive buying with hedonic motivation mediation. Meanwhile, utilitarian motivation does not seem able to mediate interpersonal and external factors to have a significant influence on consumers' impulsive buying behavior. Keywords: e-commerce, hedonic motivation, utilitarian motivation, impulsive buying.